EMPLOYMENT GENERATION THROUGH STANDARD HOTEL INDUSTRY BUSINESS: MYTHS AND REALITIES!! - Dayanandan, Dr. (IJRDO - Journal of Business Management, 2016)
Role of the modern service sector like standard hotel industries is an alternative stimulant to socio-economic development, poverty reduction and job creation and its increasing demand and supply gap. However, due to different constraints and factors, this may not be achieved the socio-economic advantages of the society through employment as expected from standard hotels investment in the study area. Hence the main objective of this paper is to assess the role of standard hotel industry business in employment gemeration. The study is based on both quantitative and qualitative in nature with the help of primary and secondary data. Primary data was collected through survey questionnaire, administered to employees and management members of sample standard hotels, selected by systematic sampling technique. Secondary data was obtained through review of literatures, regional investment data base and the regional culture and tourism bureau reports. Descriptive analysis was employed and argumentative explanations and narrations are provided from qualitative information. The findings indicate that socio-economic benefits of the society through employment generation from the standard hotel business are inefficient and instability, which is in favor of the employers rather than employees. Inefficient employment characteristics are absence of transparency and accessibility, selectiveness and low qualification. Attributes for employment instability are poor working conditions and unsuitable environment, absence of motivation, incentives and unequal treatment between management members and workers that the management members benefit better than workers because a significant number of workers cannot afford for personal savings, upgrade education and personal problems. As the results indicate, standard hotel business failed to achieve the expected socio-economic gains through employment. Further both both demand and supply side constraints are responsible for identified inefficiencies. Therefore, improving the existing operation with recommendable means of intervention is appropriate to address the problems.